Characteristics of Karst Formations and Their Significance for Shale Gas Exploration - Hu, Xiuquan; Liu, Hong; Tan, Xiucheng; Dan, Yong; He, Heng; Xiao, Chenjing; Li, Ruixue (Frontiers in Earth Science, 2022)
The classification method of karst formations is widely used in engineering and environmental geology but is seldom used in petroleum geology. In this study, the classification method of karst formations is applied to the sealing study of shale gas roof and floor carbonate rocks, and the influence on shale gas accumulation and drilling is discussed. The Paleozoic black shale in southern China is primarily formed by marine and transitional faces, and the intergrowth between shale and carbonate rocks is a basic geological feature of the Paleozoic strata in southern China. Carbonate karst is an unavoidable problem in shale gas exploration in southern China. Around the black shale target layer, in the Upper Paleozoic trait region, the study starts from the development strength of karst strata, through geological profile survey, spring flow statistics, test, and other methods and means; the shale and the carbonate rock contacted with it are taken as a whole to explore the impact of karst strata on shale gas drilling. The Upper Paleozoic karst strata in the study area were divided into two kinds, four types, and six subtypes. It was determined that the limestone continuous karst strata of the Sidazhai Formation and the second member of the Nandan Formation are the sensitive layers of shale gas drilling, whereas the first number of Nandan and Wuzhishan formations are shale reservoir-forming packers. In addition, a method for evaluating the karst sensitivity of shale gas exploration is summarized. The karst avoidance, karst-sensitive, and karst-insensitive areas for shale gas exploration were divided. Combined with the surface and underground conditions and the basic geological conditions of shale gas not being significantly different, shale gas drilling should avoid the fold core and fault zones.